UTILIZATION OF RAWAPENING PEAT FOR NUTRIENT BLOCK AS A MEDIA NURSERIES ANTHOCEPHALUS CADABA AND PARASERIANTHES FALCATARIA - Sittadewi., dkk, E. Hanggari (BPPT)
Nutrient Block is a growing medium product in the form of a square (25 x 25 cm) or cylindrical (diameter = 20 cm, height = 25 cm) made of peat which has been composted, plus adhesive gypsum or tapioca waste. Nutrient Block is designed to support the post mining land rehabilitation program that is now threatening the environmental degradation in mining areas. Nutrient Block products has been proved good for growth because of the media in addition to having physical properties that are capable of storing large amounts of water, contain enough nutrients in the form available to plants,so it can support plant growth. Results of the Nutrient Block application test to Jabon (Anthocephalus cadaba) and Sengon (Paraserianthes falcataria) plants showed that good performance, both plant height and diameter of trees and leaf growth in plants Jabon appear healthy and getting wider.keywords: nutrient block, post-mining land rehabilitation. Paraserianthes falcataria, Anthocephalus cadaba